High-Efficiency Production of Auricularia polytricha Polysaccharides Through Yellow Slurry Water Fermentation and Its Structure and Antioxidant Properties - Yang, Zhengbin; Hu, Yuedan; Wu, Jiangli; Liu, Jingui; Zhang, Furong; Ao, Hongya; Zhu, Yong; He, Laping; Zhang, Wei; Zeng, Xuefeng (Frontiers in Microbiology, 2022)
Yellow slurry water is a kind of nutrient-rich wastewater of tofu. Firstly, the medium of yellow slurry was optimized. Then, APP40, APP60 and APP80 were obtained by sedimentation with different concentration of ethanol (40%, 60% and 80%). The physicochemical properties and primary structures of the three polysaccharides were studied by high performance anion exchange chromatography (HPAEC), high performance gel filtration chromatography (HPGFC), scanning electron microscope (SEM), atomic force microscope (AFM) and Fourier transform infrared (FT-IR) spectrometer. Finally, the effects of three polysaccharides on antioxidation activity were studied. According to the experimental optimization the results, the biomass and the production of Auricularia Polytricha Polysaccharides (APPS) reached the peak, and they were 13.5 ± 0.655 g/L and 9.42 ± 0.253 g/L (p <0.05). The SEM and the AFM showed that the height of APP80 gradually increased from 31.1 nm to 46.7 nm and from APP40 to APP80. The particle size of APP80 increased, the pores decrease or even disappear, and the molecules begin to aggregate. The Fourier transform infrared spectrum analysis showed that the three polysaccharides possessed key functional groups. The carbohydrate content of APP40, APP60, and APP80 was 20.2%, 34.25% and 31.73%. The molecular weights of APP40, APP60 and APP80 are 9.462×104 Da, 8.742×104 Da and 8.091×104 Da respectively. The three polysaccharides were composed of rhamnose, galactose, glucose, mannose and xylose but with different molar ratio. APP80 showed strong reducing ability and scavenging activity of DPPH and hydroxyl radicals through antioxidant activities evaluated in vitro. This study introduces a way for the effective use of yellow slurry water.